2010
DOI: 10.1097/bpo.0b013e3181edba12
|View full text |Cite
|
Sign up to set email alerts
|

Tibial Hemimelia in One of the Identical Twins

Abstract: Tibial hemimelia, a rare congenital anomaly, is characterized by deficiency of the tibia with relatively intact fibula. The incidence of congenital deficiency of the tibia is approximately 1 per 1 million live births. The percentage of monozygotic twins is 0.8% of all newborns. Therefore, the occurrence of tibial hemimelia in monozygotic twins is 1 case per 125 million. The purpose of this article is to present a case of identical twins, in which 1 had tibial hemimelia, a double metatarsal bone and preaxial po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Werner’s syndrome [25] is an autosomal dominant disorder that is currently thought to be a variant of triphalangeal thumb-polysyndactyly syndrome (TPTPS). Both diseases have been mapped to chromosome 7q [26]. A deletion on chromosome 8q, contiguous with Langer–Giedion syndrome, or type II tricho–rhino–phalangeal syndrome (TRPS II) may also be responsible for tibial hemimelia [27].…”
Section: Introductionmentioning
confidence: 99%
“…Werner’s syndrome [25] is an autosomal dominant disorder that is currently thought to be a variant of triphalangeal thumb-polysyndactyly syndrome (TPTPS). Both diseases have been mapped to chromosome 7q [26]. A deletion on chromosome 8q, contiguous with Langer–Giedion syndrome, or type II tricho–rhino–phalangeal syndrome (TRPS II) may also be responsible for tibial hemimelia [27].…”
Section: Introductionmentioning
confidence: 99%
“…Werner first described a case of polydactyly of the hands, digitalization of the thumb, short lower limbs with aplasia of the tibias, and polydactyly of the toes in 1915 [1]. Reber [4] reported on a boy with a full manifestation of this complex anomaly whose father had triphalangeal thumbs only, and Leite et al [5] reported on a case of identical twins, one of whom had complete tibial hemimelia and preaxial polydactyly on the left side, whereas the other had no alterations at all. Vargas et al [2] reported on a family with 10 affected members spanning three generations, and Agarwal et al [3] reported on a family with seven affected members, also over three generations, who showed bilateral agenesis of the whole tibia and distal radius, five-fingered hands, and pedal polysyndactyly.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Family history of congenital anomaly of tibia, as well as intra-familial phenotypic variations of the defect in twin pregnancy has been reported. [789] The anomalies in which the number of skeletal elements increased arise during the first 7 weeks of intrauterine life. A decrease in the number of skeletal parts may arise after, as well as during, this 7-week period.…”
Section: Discussionmentioning
confidence: 99%